Long-term outcomes of cement in cement technique for revision endoprosthesis surgery - Nicholas M. Bernthal (2019)
© 2017 Wiley Periodicals, Inc. Background and Objective: Cemented endoprosthetic reconstruction after resection of primary bone sarcomas has been a standard-of-care option for decades. With increased patient survival, the incidence of failed endoprostheses requiring revision surgery has increased. Revision of cemented endoprotheses by cementing into the existing cement mantle (CiC) is technically demanding. Methods: This is a retrospective review of our endoprosthesis database of 512 consecutive cemented endoprosthetic reconstructions performed for oncologic diagnoses between 1980 and 2014. A total of 54 implants (mean patient age 32 years, range 13-81) were revised with a CiC technique. Outcomes evaluated were prosthesis survival, revision surgery categorized according to the Henderson Failure Mode Classification, complications, and functional scores. Results: Fifteen-year Kaplan-Meier survival rate was 34% for initial revision and 39% for subsequent revision implants. Mean revised Musculoskeletal Tumor Society (MSTS) Score was 27 at latest follow-up. Infection rate was 2%, 9%, and 13% for primary endoprostheses, initial revisions, and subsequent revisions, respectively. Limb salvage rate was 87%. Conclusions: At long-term follow up, endoprostheses revised with the CiC technique showed consistent 15-year survival from initial (34%) to subsequent (39%) revision. Despite a relatively high failure rate, these results are encouraging and demonstrate that this is a conservative, repeatable technique.